2015
DOI: 10.1166/jbmb.2015.1539
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biochar from Pyrolysis of Rice Husk and Rice Straw

Abstract: The valorization of rice husk biochar obtained by pyrolysis was studied by production high quality activated carbon. Activated carbon (AC) chemically treated by K 2 CO 3 , was used as sorbent phase in bar adsorptive microextraction followed by comprehensive two-dimensional gas chromatography coupled to a quadrupole mass spectrometer analysis (BAµE/GC×GC-qMS) for trace analysis of carbazole in commercial diesel. The prepared AC was characterized by N 2 adsorption, SEM-EDS and pH PZC. Assays of nitrogen adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
9
11
0
Order By: Relevance
“…CEC is an important property of biochar indicating the capacity of a biochar to adsorb cation nutrients [20]. In our study, the CEC for the generated biochars significantly decreased from 66.59 to 18.53 cmol·kg −1 when the pyrolysis temperature increased from 300 to 600 °C (Figure 2), which was consistent with previous study [44]. The shift in CEC may due to the reduction of functional groups and oxidation of aromatic C with temperature [34], which was well supported by the lower O/C ratio and our FTIR and Boehm titration results at higher temperature.…”
Section: Ph and Cation Exchange Capacitysupporting
confidence: 92%
“…CEC is an important property of biochar indicating the capacity of a biochar to adsorb cation nutrients [20]. In our study, the CEC for the generated biochars significantly decreased from 66.59 to 18.53 cmol·kg −1 when the pyrolysis temperature increased from 300 to 600 °C (Figure 2), which was consistent with previous study [44]. The shift in CEC may due to the reduction of functional groups and oxidation of aromatic C with temperature [34], which was well supported by the lower O/C ratio and our FTIR and Boehm titration results at higher temperature.…”
Section: Ph and Cation Exchange Capacitysupporting
confidence: 92%
“…Table 2 shows the biochar pH and elemental composition of both materials obtained at various pyrolysis temperatures. Between 300 • C and 700 • C, the pH of the rice-husk biochar increased from acidic (pH = 5.31) to strongly basic (pH = 9.42), which was consistent with previous studies (pH = 5.37-9.82) [16], while the pH of the cotton-straw biochar increased from neutral (pH = 6.61) to strongly basic (pH = 10.42). A previous study found that the pH of biochar typically ranges from 4 to 12 [17], and the results of the present study fell within that range.…”
Section: Data Processingsupporting
confidence: 91%
“…The factors affecting CEC include (a) surface structure, (b) surface area and (c) functional groups (such as phenolic, hydroxyl and carbonyl groups) (Claoston et al, 2014; Liang et al, 2006). As the pyrolysis temperature increased from 300°C to 500°C, the CEC decreased as reported by other studies (Phuong et al, 2015; Zhao et al, 2017). Numerous research works have reported the reduction of CEC with increasing temperature and pyrolysis (Claoston et al, 2014; Zornoza et al, 2016).…”
Section: Discussionsupporting
confidence: 83%